FORWARDING SALES FORECASTING ANALYSIS OF FREIGHT FORWARDING SERVICES AT PT. GLOBAL DRAGON OCEAN - Dewi Rakhmadani; Ade Suryana; Endro Andayani (International Journal of Social Science, 2023)
This study aims to find out how to forecast and predict the number of sales of freight forwarding services at PT Samudera Naga Global. This research was conducted using autoregression and exponential smoothing methods. The author conducts research on companies engaged in the transportation of goods that manage all or part of the activities related to the delivery and receipt of goods through transportation routes. The results of the research were carried out using two methods, namely autoregression and exponential smoothing by comparing the smallest error rate, indicating the best and most appropriate forecasting method for PT Samudera Naga Global's sales forecasting, namely the autoregression method with a MAD value of 127,428.55, MSE of 22,985. 627,066.65.